LAW ENFORCEMENT AND FIREFIGHTERS PHYSICAL ACTIVITY STUDY - Holsinger, Jourdyn (East Carolina University, 2020)
Law enforcement and firefighters serve a vital role in maintaining the safety and order in our communities. They suffer from numerous health problems including heart disease, psychological stress and sleep disorders. Their jobs are stressful and at times, life-threatening. The stress associated with these professions can have a negative effect on their physical, mental, and occupational health. These stressors may increase obesity, fatigue, and cardiovascular disease; decrease quality of life and satisfaction with life; and lead to burnout and compassion fatigue. Among other working populations, physical activity has been shown to provide health benefits, but limited research exists in this population. PURPOSE: The purpose of this study is to examine the relationships between physical activity levels and measures of physical, mental, and occupational health in firefighters and law enforcement officers. Physical health is defined as body mass index (BMI), fatigue, and sleep quality. Mental health is defined as quality of life (QOL), stress, and satisfaction with life. Occupational health is defined as compassion fatigue and job stressors. METHODS: Law enforcement officers and firefighters (N = 51; 35.1 ± 10.5 years; 88% Male; 80% Caucasian) were assessed for physical activity via the Fitbit Flex activity tracker over a 7-day period and the International Physical Activity Questionnaire (IPAQ). Body mass index was measured using height and weight measurements. Each of the remaining measures of health were assessed via questionnaires. Pearson correlations were used to determine the relationship between subjective and objective physical activity and each of the measures of physical, mental and occupational health. RESULTS: Vigorous (IPAQ) physical activity (VPA) had a significant moderate, negative association with BMI (r = -.31, p [less-than .05), systolic (r = -.29, p [less-than] .05) and diastolic blood pressure (r = -.28, p [less-than] .05). BMI was negatively correlated with sleep quality from the Pittsburgh Sleep Quality Index (PSQI) (r = -.46, p [less-than] .01), and positively related with systolic (r = .97, p [less-than] .01), and diastolic (r = .97, p [less-than] .01) blood pressures. Waist-to-hip ratio was significantly correlated with occupational moderate intensity (IPAQ) physical activity (r = .32, p [less-than] .05), general fatigue (r = -.35, p [less-than] .01), mental fatigue (r = - .32, p [less-than] .05), and PSQI (r = -.31, p [less-than] .05). There was a significant negative relationship between stress and the mental component of the QOL (r = -.40, p [less-than] .01). Walking (IPAQ) and personal accomplishment (r = .34, p [less-than] .05) had a significant moderate, positive association. Burnout was moderately, significantly correlated with secondary traumatic stress (r = .46, p [less-than] .01), emotional exhaustion (r = .40, p [less-than] .01), and depersonalization (r = .31, p [less-than] .05). No significant relationships found between total physical activity measured through the Fitbit and physical, mental or occupational health. These results provide evidence that there is an association between activity gathered from IPAQ-long form and physical and occupational health measures such as BMI, blood pressure, and personal accomplishment. CONCLUSION: The stressors that comes from job demands for law enforcement officers and firefighters are negatively related to their physical, mental and occupational health. Due to these stressors, it is critical to create solutions to help lower the risk of stress and improve measures of health in both populations. The results of this study provide evidence that there are health benefits with physical activity among law enforcement and firefighters in eastern North Carolina. Future studies that focus on either physical activity intervention or a worksite-based physical activity promotion program are needed to fully understand the effects of physical activity could have on physical, mental and occupational health in these occupations.
Keywords: Police--Health and hygiene; Fire fighters--Health and hygiene; Exercise--Physiological aspects; Burn out (Psychology)